2021
DOI: 10.1002/mnfr.202100152
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gut Microbiota in the Anti‐Colitic Effects of Anthocyanin‐Containing Potatoes

Abstract: Scope Anthocyanin‐containing potatoes exert anti‐inflammatory activity in colitic mice. Gut bacterial dysbiosis plays a critical role in ulcerative colitis. This study examined the extent to which the anti‐colitic activity of anthocyanin‐containing red/purple‐fleshed potatoes depends on the gut bacteria using a chemically‐induced rodent model of colitis with the intact and antibiotic‐ablated microbiome. Methods and Results Four‐week‐old male mice (C57BL6) are randomly assigned to the control diet or 20% purple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…It is well known that ulcerative colitis is an inflammatory disease characterized by substantial pro-inflammatory responses and several inflammatory pathways such as NF-κB, STATs, and MAPK are involved. 29 We hypothesized that BAs-ZnNPs would inhibit NF-κB activation-mediated inflammation by down regulation of COX-2 level, as our results show that BAs-ZnNPs inhibit, both NF-κB-induced pro-inflammatory cytokines and COX-2-induced prostaglandin production causing inflammation. COX-2 is expressed at low levels in healthy mucosa and during UC remission but observed that its expression levels are significantly increased in active UC.…”
Section: Discussionmentioning
confidence: 86%
“…It is well known that ulcerative colitis is an inflammatory disease characterized by substantial pro-inflammatory responses and several inflammatory pathways such as NF-κB, STATs, and MAPK are involved. 29 We hypothesized that BAs-ZnNPs would inhibit NF-κB activation-mediated inflammation by down regulation of COX-2 level, as our results show that BAs-ZnNPs inhibit, both NF-κB-induced pro-inflammatory cytokines and COX-2-induced prostaglandin production causing inflammation. COX-2 is expressed at low levels in healthy mucosa and during UC remission but observed that its expression levels are significantly increased in active UC.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the prototypical nuclear factor kappa B (NF-κB) is a principal signaling pathway of inflammation and an end point for other pathways . All cells in the tumor microenvironment are regulated by the NF-κB signaling pathway and influence the onset and progression of inflammation and cancer .…”
Section: Mechanisms Underlying the Effects Of Anthocyaninsmentioning
confidence: 99%
“…Prebiotics, including mannose, glucan, inulin and fructan, and probiotics like Lactobacillus and Bifidobacterium , have been proven to regulate the gut microbiota, which is of great significance for improving host intestinal health . Similarly, due to the various physiological activities and prebiotic effect of anthocyanins, several studies have demonstrated anthocyanins’ effects in preventing and managing the intestinal diseases. …”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has associated flavonoid intake with the alleviation of experimental colitis, 11–15 with the majority of the studies using either whole-food or purified flavonoids as a source. Albeit observations of some protective effects, the complexity of the food matrix makes it difficult to pinpoint the contributions of any single component.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In turn, gut microbiota could impact the bioavailability of flavonoids by exhibiting a diverse spectrum of functions in the bioconversion of flavonoids including degly-cosylation, oxidation, demethylation, and catabolism of flavonoids into phenolic acids. 9,10 Growing evidence has associated flavonoid intake with the alleviation of experimental colitis, [11][12][13][14][15] with the majority of the studies using either whole-food or purified flavonoids as a source. Albeit observations of some protective effects, the complexity of the food matrix makes it difficult to pinpoint the contributions of any single component.…”
Section: Introductionmentioning
confidence: 99%